Social Perception Deficit as a Factor of Vulnerability to Psychosis: A Brief Proposal for a Definition - Cavieres, Álvaro; López-Silva, Pablo (Frontiers in Psychology, 2022)
Disturbances in social cognition are a core features of schizophrenia. While most research on the field has focused on emotion perception, social knowledge, theory of mind, and attribution styles; the domain of social perception has received little specific attention. In this paper, we suggest that this issue can be explained by the lack of a precise and unitary definition of the concept, this leading to the existence of different competing uses of the concept and their conflation with other domains of social cognition. Relying on resources coming from the ecological approach to psychology and the phenomenological tradition in psychiatry, we propose that the concept of Social Perception should be used to refer to low-level pre-reflective processes underlying the awareness of interpersonal interactions with and between others. Clinical evidence suggests that people with schizophrenia have problems perceiving social situations as opportunities for social engagement, so, in order to fulfill this explanatory need, we propose that the term should be useful to capture this important yet neglected domain of social cognition. We conclude with the discussion of some future directions for research derived from our proposal.